Antibiotic resistance among Salmonella enterica serovars Typhi and Paratyphi A in Pakistan (2001-2006) - Rumina Hasan; Afia Zafar; Zohair Abbas; Vikram Mahraj; Faisal Malik; Anita Zaidi (Journal of Infection in Developing Countries)
Objectives: To compare antimicrobial resistance in S. Typhi and S. Paratyphi A isolates from Pakistan. Methods: Blood samples were collected through > 175 laboratory collection points in major cities and towns across the country. The study included 3,671 S. Typhi and 1,475 S. Paratyphi A isolates (2001-2006). Multidrug resistance (MDR) was defined as resistance to first-line agents co-trimoxazole, chloramphenicol and ampicillin. Results: In total, 79.3% S. Typhi and 59.9% S. Paratyphi A were isolated from patients under 15 years of age. During the study period, the MDR rate increased in S. Typhi (34.2 to 48.5% p